2017
DOI: 10.4103/ijph.ijph_369_16
|View full text |Cite
|
Sign up to set email alerts
|

Status of early childhood education under integrated child development services scheme in Bankura Municipality, West Bengal

Abstract: For the preparation of formal schooling of children most important needs of the hour are physical facility of AWCs, supportive supervision of AWWs, and creation of congenial environment at home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In addition, only 10% of centres had sufficient floor space for indoor activities, 33% did not have any materials for activities, and none ran activities that were age appropriate. One study found that only 33% of children enrolled at the centre remained to participate in ECE [38].…”
Section: Integrated Child Development Scheme (Icds)mentioning
confidence: 99%
“…In addition, only 10% of centres had sufficient floor space for indoor activities, 33% did not have any materials for activities, and none ran activities that were age appropriate. One study found that only 33% of children enrolled at the centre remained to participate in ECE [38].…”
Section: Integrated Child Development Scheme (Icds)mentioning
confidence: 99%
“…Burnout is highly correlated with stress perception (Botha et al, 2015). Mitra et al (2018) demonstrated that a person's perception of stress significantly and directly mediated their level of burnout. Not only does a nurse's perception of stress directly affect their level of burnout (Jaracz et al, 2005) but the increased perception of stress may also mediate the relationship between work–life balance and burnout.…”
Section: Introductionmentioning
confidence: 99%